2019
DOI: 10.1111/jomf.12582
|View full text |Cite
|
Sign up to set email alerts
|

Marital Strain and Psychological Distress in Same‐Sex and Different‐Sex Couples

Abstract: Objective: This study examines the association of marital strain-as reported by each spouse-with psychological distress and considers whether the associations vary for men and women in gay, lesbian, and heterosexual marriages. Background: Prior studies show that marital strain is associated with psychological distress. However, most studies rely on only one spouse's perspective and do not consider how appraisals of strain from both spouses may contribute to distress. Moreover, possible gender differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Beyond these population trends, a novel component of research on relationships and health is an attempt to explain these health trends and differences, typically with qualitative data. For example, qualitative and daily diary research suggests that gay and lesbian couples appear to be more concordant in health behavior (Holway, Umberson, & Donnelly, ; Reczek, ; Reczek & Umberson, ), are more likely to care for each other when sick (Thomeer, Reczek, & Umberson, ; Umberson, Thomeer, Reczek, & Donnelly, ), and are differentially impacted by marital strain (Garcia & Umberson, ) than heterosexual couples. Moreover, it appears that gay and lesbian couples face higher levels of discrimination and stress than heterosexual couples (Cao et al, ; Frost et al, ), and marriage bans are shown to worsen health among SGM people (Hatzenbuehler et al, , ; Kail, Acosta, & Wright, ).…”
Section: Sgm Intimate Relationshipsmentioning
confidence: 99%
“…Beyond these population trends, a novel component of research on relationships and health is an attempt to explain these health trends and differences, typically with qualitative data. For example, qualitative and daily diary research suggests that gay and lesbian couples appear to be more concordant in health behavior (Holway, Umberson, & Donnelly, ; Reczek, ; Reczek & Umberson, ), are more likely to care for each other when sick (Thomeer, Reczek, & Umberson, ; Umberson, Thomeer, Reczek, & Donnelly, ), and are differentially impacted by marital strain (Garcia & Umberson, ) than heterosexual couples. Moreover, it appears that gay and lesbian couples face higher levels of discrimination and stress than heterosexual couples (Cao et al, ; Frost et al, ), and marriage bans are shown to worsen health among SGM people (Hatzenbuehler et al, , ; Kail, Acosta, & Wright, ).…”
Section: Sgm Intimate Relationshipsmentioning
confidence: 99%
“…Relationships are a key part of women's lives and their identities (Simon & Barrett, 2010;Whitton & Kuryluk, 2014). Stress is strongly associated with relationship stress and problems (Horwitz, White, & Howell-White, 1996;Randall & Bodenmann, 2017) which in turn are associated with distress (Garcia & Umberson, 2019), particularly for women (Garcia & Umberson, 2019;Proulx, Helms, & Buehler, 2007). However these associations are not well-understood in queer women's relationships which may be disproportionately affected by multiple sources and levels of stress due to the marginalization of both the individuals and the relationship.…”
Section: Stress and Relationshipsmentioning
confidence: 99%
“…The strain of stressful relationships may be disproportionately detrimental to queer women given that it may compound the effects stigma, discrimination, and lower levels of overall social support . However, recent research suggests that in comparison to women who are married to men, women in same-sex marriages may evince less of an association between relationship strain and distress, possibly due to the lower gendered power differentials in same-sex relationships (Garcia & Umberson, 2019) or because external stressors may bring couples closer together (Reczek, 2015). Given the importance of stable and positive relationships to health, it is imperative for research to shed investigate whether stressors faced by queer women may strain relationships.…”
Section: Individual Level Versus Couple-level Minority Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research indicates that marriage is important for same‐sex couples (SSCs), providing evidence of the benefits associated with marriage, including lower levels of psychological distress (Wight et al, 2013) and better health (Denney et al, 2013; Liu et al, 2013), relative to their unmarried cohorts. The evidence suggesting that benefits accrue to married individuals motivates researchers to explore antecedents and deterrents of same‐sex marriage (SSM) (Garcia & Umberson, 2019; Gates, 2015; Gates & Brown, 2015; Ocobock, 2018; Verbakel & Kalmijn, 2014).…”
Section: Introductionmentioning
confidence: 99%